The effectiveness of promotional tools: the case of TM Centrex in Telekom Malaysia(TM), Seremban Negeri Sembilan / Zariah Kassim (Faculty of Business and Management, 2007)
This research was carried out to obtain information about the effectiveness of promotional tools that have been used by Telekom Malaysia, Negeri Sembilan to promote and enhances the demands of TM Centrex among the business customers in Negeri Sembilan. This study was based on systematic sampling method using the list names of the companies in Negeri Sembilan that have subscribe to TM Centrex with Telekom Malaysia. The overall findings of frequency from 50 respondents shows that majority of the users that subscribe TM Centrex is from manufacturing sector (30.0%), and the less sector that subscribe is constructions (12.0%). Meanwhile the average mean for loyalty among the respondents towards Telekom Malaysia is 3.9800, factor of satisfaction is carry average mean of 3.9400, level of retention have average mean of 3.7800 and seNice quality, the average mean is 3.6800. The findings conclude from the five factors that have analyzed in this study for the promotional tools elements, there have two factors do not have a significant relationship with the effectiveness of the promotional tools as every P value for each factors resulted P> 0.05 which P =0.149>0.05 for Technical advisory seNice and P = 0.088>0.05 for advertising. It is found that the advertising and Technical advisory service that have been used by Telekom Malaysia, Negeri Sembilan in order to promote TM Centrex should be improved because the users is not satisfied with the advertising and the personal selling whereby the staffs of Telekom Malaysia is irregular to make a visit to the users place after they customers have subscribe to TM Centrex. Recommendation and suggestion on how to improve the effectiveness of the promotional tools to promote TM Centrex have been identified to help TM achieved their target and improved any weaknesses.